a + b = 8
a + c = 13
b + d = 8
c - d = 6
пусть b = x
тогда a = 8 - x
c = 13 - (8 - x)
d = 8 - x
c - d = (13 - (8 - x)) - (8 - x) = 6
13 - 8 + x - 8 + x = 6
2x - 3 = 6
2x = 9
x = 4.5
b = 4.5
a = 8 - x = 3.5
d = 8 - x = 3.5
c = 13 - (8 - x) = 13 - 3.5 = 9,5
a + b = 8
a + c = 13
b + d = 8
c - d = 6
пусть b = x
тогда a = 8 - x
c = 13 - (8 - x)
d = 8 - x
c - d = (13 - (8 - x)) - (8 - x) = 6
13 - 8 + x - 8 + x = 6
2x - 3 = 6
2x = 9
x = 4.5
b = 4.5
a = 8 - x = 3.5
d = 8 - x = 3.5
c = 13 - (8 - x) = 13 - 3.5 = 9,5